Internationalization knowledge towards performance among export oriented organizations in Malaysia - Muhammad Amir, Pawennari (2020)
Globalization has stimulated international trade and influenced a growing number of organizations to engage in the internationalization process. Building upon the insights of the resource-based view theory, the purpose of this study is to establish the antecedents and the outcomes of internationalization knowledge in the context of export-oriented organizations in Malaysia. The antecedents include international ambidexterity, external environmental factors, dynamic marketing capability and market orientation as its dimensions, with the expected outcome of export performance. This study bridged the gap by linking the organizational level of internationalization knowledge within its capability and resources to achieve export performance. This study has utilized a survey-based approach to collect the data. The sample consisted of 370 mid-tier companies operating in multiple industries in Malaysia as registered with MA TRADE database. Structural equation modeling analysis of Smart PLS was used to test the hypothesized model. The direct effects of all variables and market orientation on the export performance were positively significant. The results validated the claim that by explicitly describing these internationalization knowledge assets, the exporting activities within an organization can more effectively leverage knowledge and improve performance. Therefore, this study extended further empirical evidence on internationalization knowledge and export performance in the multi-industries of emerging economies context. The dissertation presented an internationalization knowledge framework to describe distinctly separate sources of knowledge within organizations. These knowledge sources are constructed as knowledge capabilities and resources that can allow the organization to engage in international operations particularly in export business more successfully. The theoretical and practical implications of the study as well as suggestions for future studies were also discussed.